Radiant floor cooling systems - A measurement and simulation study - Johnsson, Josef; Westerlund, Linnéa (My University, 2012)
Radiant floor cooling systems have been around for quite some time now, but are not extensively used or much talked about in the industry. The background for this thesis lies in a question formulated by a HVAC – consultancy firm, wanting to know if the radiant floor cooling system they had installed worked in an adequate way regarding given cooling effects. Other issues raised were the precision of current calculation methods as well as important design factors to retrieve a high cooling effect. The question was broadened to consider the effect of the system on the thermal climate, where mainly temperature profiles and surface temperatures were studied. The thesis is divided into one simulation- and one measurement study. The measurement study is, of course, study specific, and an atrium in the Centre of Gothenburg is studied. The measurements are mainly conducted to study the thermal climate in the atrium, as well as retrieve in data to the cooling effect calculations. Through simulations the in data was altered yielding different scenarios (i.e. with and without floor cooling), investigating the impact on the thermal climate. To retrieve as high cooling effect as possible, the thickness and thermal conductivity of the screed are important factors. Other important factors, more connected to the balancing of the system, are water temperatures and flows. When the cooling effect was calculated, a finding was that the current method to approximate the cooling effect was not accurate enough. As for the results from the measurement study; they show a clear effect from the radiant floor cooling system on the temperature levels on the first floors. Higher up in the atrium the effect is not as evident. Some study specific and general recommendations were found in this thesis; among them were the importance of thoroughly thinking through the activities and room conditions. A discussion concerning the viability of the system concludes the thesis, and the answer to the question is; it depends, partly on the activities in the room.
Keywords: Byggnadsteknik; Building Futures; Building engineering; Building Futures